Alusi Anti-Imperial dalam Misi Universal: Elaborasi Matius 28:18-20 - Prabowo, Paulus Dimas (Jurnal Teologi dan Pelayanan Kerusso, 2024)
Matthew 28:18-20 is unique material from Matthew that is not found in other synoptic gospels. Considering the political situation under Roman imperialism and the initial recipients' Jewish background, it is worth asking how Matthew structured his unique material so that it was relevant to the conditions prevailing at that time. The purpose of this article is to prove that there are allusions to the Old Testament in Matthew 28:18-20 so that the intended use can be understood and fits the context. The methods used are structural analysis, style analysis, and allusion analysis. The results of the discussion prove that Matthew 28:18-20 contains allusions to Daniel 7:13-14 and Isaiah 7:14; 8:8,10 which is anti-imperial in nature so that recipients of Matthew's Gospel are given the basis and encouragement for courage in carrying out the Great Commission even in a situation of Roman imperialism.